Analysis of the potential market segmentation of new CIAT forage hybrids in Africa, Latin America and Asia - Junca Paredes, John Jairo; Florez, Jesus Fernando; Sotelo Cabrera, Mauricio Efren; Burkart, Stefan (2024)
In developing countries, livestock farming provides a livelihood for vulnerable populations. In Africa, low productivity and quality of pastures characterize the livestock sector. In Latin America and the Caribbean (LAC), although there is greater availability of land, extensive grazing systems with low yields and no environmental sustainability are common. In Southeast Asia, cut-and-carry systems appear to have financial advantages. CIAT, together with its strategic partner Grupo Papalotla, is developing new forage hybrid seeds, i.e., interspecific Urochloa, Megathyrsus maximus and Urochloa humidicola, with better adaptation to the environmental and productive characteristics of these regions. The objective of this study is to estimate the potential markets for these materials under development. Using production assumptions, geographic profiling studies, and information on the distribution of forage species, the potential market size is calculated. In Africa, for interspecific Urochloa and Megathyrsus maximus hybrids, there would be a total potential market of 934,654 ha. Ethiopia, Kenya, Tanzania, and Uganda have a market share of 82.64%. In Southeast Asia, for the same materials, the total potential market would be 1,895,880 ha. Indonesia, Cambodia, and the Philippines have a share of 88.61%. Finally, in Latin America, the potential markets for interspecific Urochloa, Urochloa humidicola, and Megathyrsus maximus hybrids could reach up to 5,959,910 ha, 4,606,710 ha and 2,509,847 ha, respectively. The largest markets are in Brazil, Colombia, Mexico, and Venezuela with a combined share of over 90%. In all regions there are possibilities for growth for the improved forage seed sector. However, along with these advances, an institutional framework is needed to facilitate the market conditions for the distribution and adoption of such new materials.